Pengembangan Centralized Smarthome Simulator Sebagai Solusi Penghematan Biaya Listrik Menggunakan Algoritma K-Means - Putri Laras Rinjani; Edita Rosana Widasari; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The efficiency of electricity usage is less concerned in our daily life. It can be seen by lots of people who wasting electricity by using electronic devices excessively. For example, people forgot to turn off their electronic devices when they leave their house, it resulted in wasted electricity usage. To resolve the problem above, The researcher would like to implement a centralized smart home system that could save electricity bills using K-Means algorithm. Inside the system that has been developed by the researcher, it will work automatically by using the result of K-Means algorithm learning process based on user behavior in using electronic devices, so it will know when the devices should be turned on or turned off. The result of K-Means algorithm learning process is an optimal schedule to turn the electronic devices on and off. Based on the optimal schedule, the system will automatically control when the electronic devices will be turned on or off, which has been tested using simulator with 100% accuracy. Moreover, the system is able to calculate the percentage of cost efficiency in electricity usage, which has been tested to six different users with the result of cost saving percentage that each user get is 7.345%, 6.554%, 4.398%, 9.62%, 12.471%, and 7.69%.